Summertime tropospheric ozone enhancement associated with a cold front passage due to stratosphere‐to‐troposphere transport and biomass burning: Simultaneous ground‐based lidar and airborne measurements. Issue 2 (24th January 2017) - Kuang, Shi; Newchurch, Michael J.; Johnson, Matthew S.; Wang, Lihua; Burris, John; Pierce, Robert B.; Eloranta, Edwin W.; Pollack, Ilana B.; Graus, Martin; de Gouw, Joost; Warneke, Carsten; Ryerson, Thomas B.; et al.
Abstract: Stratosphere‐to‐troposphere transport (STT) and biomass burning (BB) are two important natural sources for tropospheric ozone that can result in elevated ozone and air‐quality episode events. High‐resolution observations of multiple related species are critical for complex ozone source attribution. In this article, we present an analysis of coinciding ground‐based and airborne observations, including ozone lidar, ozonesonde, high spectral resolution lidar (HSRL), and multiple airborne in situ measurements, made on 28 and 29 June 2013 during the Southeast Nexus field campaign. The ozone lidar and HSRL reveal detailed ozone and aerosol structures as well as the temporal evolution associated with a cold front passage. The observations also captured two enhanced (+30 ppbv) ozone layers in the free troposphere (FT), which were determined from this study to be caused by a mixture of BB and stratospheric sources. The mechanism for this STT is tropopause folding associated with a cutoff upper level low‐pressure system according to the analysis of its potential vorticity structure. The depth of the tropopause fold appears to be shallow for this case compared to events observed in other seasons; however, the impact on lower tropospheric ozone was clearly observed. This event suggests that strong STT may occur in the southeast United States during the summer and can potentially impact lower troposphere during these times. Statistical analysis of the airborne observations of trace gases suggests a coincident influence of BB transport in the FT impacting the vertical structure of ozone during this case study. Key Points: Ozone structures associated with a cold front passage Simultaneous ozone lidar, ozonesonde, aerosol lidar, and airborne in situ measurements Mixed influence of biomass burning and stratosphere‐to‐troposphere transport on tropospheric ozone